Fireman sam and the treetop adventure - Jenner, Caryn (Egmont Books Great britain, 1997)
A mini-edition story of the day Norman Price pretends to be a cat and gets stuck up a tree. Fireman Sam and the Pontypandy Fire Brigade come to the rescue.